Implementasi Program Kajian Kitab Ta’lim Muta’allim Dalam Pembentukan Akhlakul Karimah Siswa Di Sekolah Menengah Kejuruan Terpadu Ad-Dimyati Kota Bandung - Miftakhul Anam; Ayi Sobarna (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. In the era of globalization, moral degradation and a lack of proper etiquette among adolescents have become increasingly prevalent. SMK Terpadu Ad-Dimyati has introduced the Ta’lim Muta’allim study program to cultivate students' noble character (akhlaqul karimah) and address issues of disrespectful behavior (su'ul adab) in learning, communication, and social interactions. This study aims to analyze the implementation of this program in shaping students' moral character. A qualitative descriptive method with a case study approach was employed. Data were collected through observations, in-depth interviews, and documentation. The findings indicate that the program's implementation comprises three main stages: (1) Planning, which includes setting objectives, developing lesson plans (RPP), and ensuring the availability of qualified teachers, funding, and infrastructure; (2) Implementation, consisting of opening activities such as tawasulan and collective prayers, core learning activities utilizing the bandongan method, reinforcement strategies, Q&A sessions, and tausiyah (student-led sermons) as a concluding activity; (3) Evaluation, conducted through munaqosah (oral examinations) to assess students’ understanding and regular meetings to review challenges and program improvements. The study concludes that the program effectively enhances students' etiquette, discipline, sense of responsibility, and spiritual awareness. Furthermore, it contributes to character education based on Islamic values, which can be applied in various educational institutions. This study serves as a reference for other schools seeking to develop similar programs and provides recommendations for future research on the implementation of classical Islamic texts in character education within formal non-pesantren schools. Abstrak. Pada era globalisasi, degradasi moral dan kurangnya adab di kalangan remaja semakin meningkat. SMK Terpadu Ad-Dimyati menghadirkan program kajian kitab Ta’lim Muta’allim untuk membentuk akhlakul karimah siswa dan mengatasi perilaku su'ul adab dalam belajar, berbicara, dan berinteraksi. Penelitian ini bertujuan menganalisis implementasi program tersebut dalam pembentukan akhlakul karimah siswa. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi program terdiri dari tiga tahap utama: (1) Perencanaan, meliputi penetapan tujuan, penyusunan RPP, serta penyediaan guru, anggaran, dan sarana prasarana; (2) Pelaksanaan, mencakup kegiatan pembuka dengan tawasulan dan doa bersama, pembelajaran inti menggunakan metode bandongan serta strategi pengulangan materi, tanya-jawab, serta tausiyah siswa sebagai penutup; (3) Evaluasi, dilakukan melalui sidang munaqosah untuk menilai pemahaman siswa dan rapat rutin guna meninjau kendala serta perbaikan program. Hasil penelitian menunjukkan bahwa program ini efektif dalam meningkatkan adab, disiplin, tanggung jawab, dan kesadaran spiritual siswa. Program ini juga memberikan kontribusi dalam pendidikan karakter berbasis Islam yang dapat diterapkan di berbagai institusi pendidikan. Penelitian ini diharapkan menjadi referensi bagi sekolah lain dalam mengembangkan program serupa serta rekomendasi bagi penelitian selanjutnya untuk mengkaji lebih dalam implementasi kitab klasik dalam pendidikan karakter di sekolah formal non-pesantren.